Students’ Class Perceptions and Ratings of Instruction: Variability Across Undergraduate Mathematics Courses - Wilkins, Jesse L. M.; Jones, Brett D.; Rakes, Lee (Frontiers in Psychology, 2021)
The primary purpose of this study was to examine whether students’ motivation-related perceptions of mathematics courses were related to their ratings of instruction while controlling for their academic major, type of math class, and expected grade in the class. We investigated these relationships at both the student- and class-level because little is known about whether students’ motivation-related perceptions vary across mathematics courses and whether this variance is related to overall class ratings of instruction. The sample included 795 students nested within 43 different mathematics course sections. Students provided their course perceptions of autonomy, utility value, expectancies for success, situational interest, instructor caring, expected grade, and their overall perceptions of the course and instructor. Multilevel modeling techniques were used to investigate potential student- and class-level effects as well as compositional effects. Students’ class perceptions varied significantly across mathematics courses. In addition, students’ motivation-related course perceptions were positively related to their instructor and course ratings at both the student-level and class-level; however, the strength of these relationships sometimes varied across courses for some of the motivation-related perceptions. These results suggests that the motivational climate (i.e., the psychological environment) can affect students’ instructor and course ratings. Moreover, these findings indicate that instructors have some control over their instructor and course ratings through the teaching strategies that they implement. For example, they may be able to increase their ratings by implementing teaching strategies that support students’ autonomy, goals, success, interests, and relationships.